Toward a comprehensive measure of socio-cultural diversity: The case of Germany - Milad Abbasiharofteh; Tom Brökel (Spatial transformation: Processes, strategies, research design, 2022)
The positive impact of socio-cultural diversity on innovation and economic prosperity has been widely discussed. Yet, there is a lack of a clear quantitative indicator of sociocultural diversity. Most empirical works are limited to small case studies that follow various methods. This gap in the literature calls for a comprehensive measure whereby researchers could assess and compare diversity across cities and regions at the national level. Building on a unique database of registered associations (in German: eingetragene Vereine), this study provides a hierarchical categorization of associations based on their field of activities. Applying the Shannon entropy index, the sociocultural diversity of German regions is measured. The findings indicate a disparity between East and West Germany, reflecting the path-dependent nature of historical events. This article sets an agenda for future research.
urn:nbn:de:0156-08910764; hdl:10419/251347; https://econpapers.repec.org/RePEc:zbw:arlfob:19
Keywords: 710; Socio-cultural diversity; associations; innovation; German regions